Exploring constraining factors for use of private sector finance in delivery of public sector infrastructure in Tanzania: A qualitative study - Kavishe, Neema; Zulu, Sambo Lyson; Luvara, Valentine; Zulu, Ephraim; Musonda, Innocent; Moobela, Cletus; Chileshe, Nicholas (Frontiers in Built Environment, 2023)
While governments remain accountable for the delivery of infrastructure services, given the paucity of public resources, studies have recommended the use of private sector finance (PSF) as an alternative approach to delivering sustainable infrastructure both in developed and developing economies. Despite the recommendation, there has been very little use of PSF in delivering public projects, particularly in sub-Saharan Africa. Therefore, this study explores the constraining factors for the use of PSF in the delivery of public infrastructure in Tanzania and proposes recommendations. A total of 10 semi-structured interviews were conducted with different stakeholders delivering public infrastructure services. Interviewees were purposefully selected. Data were analyzed through conceptual content analysis. The findings reveal that the top five constraining factors were inadequate knowledge and skills, lack of policy to support or suffice PSF, bureaucracy or delays of approvals, lack of proper models for PSF, and lack of skilled people or existence of a big national skill gap. Thus, the identified constraints provided useful insights and were used as a road map for suggesting appropriate solutions to enhance the use of PSF. Furthermore, this is the first study to empirically explore the constraining factors for PSF in delivering infrastructure projects in the Tanzanian context.